Criminalization of Community-based Ecotourism (CBET) in Indonesia: The Cases of Pari Island, Kepulauan Seribu - shanty, janthi dharma; Priambodo, Bono Budi (UI Scholars Hub, 2023)
Pari islanders have revamped their island into cultural ecotourism destination since 2010. It has been successful because the activities have diverted the islanders’ dependence on the hard-pressed local coastal and fisheries resources and supplemented their income. This is a win-win situation the Indonesian government seeks to create with the 2007 Coastal Zone and Small Islands Management Law where natural conservation benefits local populace economically. The Law stipulates, among others, that community participation is one of the integrated coastal zone management principles. The Law also prioritizes coastal zones for conservation and tourism activities. Pari islanders thus have already implemented the imperatives of the 2007 Coastal Zone and Small Islands Management Law. However, in 2015 PT. Bumi Pari Asri (PT. BPA), a real estate development company, claimed to possess the ownership and building right certificates of 90 percent of land in Pari Island and intends to build luxurious resort there. Since then, tensions, even open conflicts, erupted between the company and Pari islanders. In 2017 several Pari islanders were apprehended by the Police due to criminal allegations of extortion, land grabbing, and trespassing. In fact, three islanders have been detained for 6 months and allegedly tortured in the detention. The islanders suspected that these cases are related to their conflicts with PT. BPA. This article basically argues that the criminal indictments against Pari islanders constitute criminalization of community-based ecotourism (CBET) which ironically is encouraged and protected, among others, by the government policy i.e., the 2007 Coastal Zone and Small Islands Management Law. To support the argument, the article exposes, clarifies, and analyzes the development of cultural and ecotourism in Pari Island, Indonesian policies on CBET in coastal zone and small islands, and the criminal cases involving the proponents and managers of CBET in Pari Island.